A retrospective analysis of cross‐reacting cetuximab IgE antibody and its association with severe infusion reactions. (9th October 2014) - Maier, Sabine; Chung, Christine H.; Morse, Michael; Platts‐Mills, Thomas; Townes, Leigh; Mukhopadhyay, Pralay; Bhagavatheeswaran, Prabhu; Racenberg, Jan; Trifan, Ovidiu C.
Abstract Severe infusion reactions (SIRs) at rates of 5% or less are known side effects of biological agents, including mAbs such as cetuximab. There are currently no prospectively validated risk factors to aid physicians in identifying patients who may be at risk of experiencing an SIR following administration of any of these drugs. A retrospective analysis of 545 banked serum or plasma samples from cancer patients participating in clinical trials of cetuximab was designed to evaluate whether the presence of pretreatment IgE antibodies against cetuximab, as determined by a commercially available assay system, is associated with SIRs during the initial cetuximab infusion. Patients with a positive test indicating the presence of pretreatment antibodies had a higher risk of experiencing an SIR; however, at the prespecified cutoff utilized in this analysis, the test has a relatively low‐positive predictive value (0.577 [0.369–0.766]) and a negative predictive value of 0.961 (0.912–0.987) in an unselected patient population. Data collected in this large retrospective validation study support prior observations of an association between the presence of pretreatment IgE antibodies cross‐reactive with cetuximab and SIRs. Further analysis of the test's ability to predict patients at risk of an SIR would be required before this assay could be used reliably in this patient population.